2017
DOI: 10.3390/s17010146
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Benefits and Accuracy of Continuous Glucose Monitoring Systems in Critically Ill Patients—A Systematic Scoping Review

Abstract: Continuous Glucose Monitoring (CGM) systems could improve glycemic control in critically ill patients. We aimed to identify the evidence on the clinical benefits and accuracy of CGM systems in these patients. For this, we performed a systematic search in Ovid MEDLINE, from inception to 26 July 2016. Outcomes were efficacy, accuracy, safety, workload and costs. Our search retrieved 356 articles, of which 37 were included. Randomized controlled trials on efficacy were scarce (n = 5) and show methodological limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 74 publications
(140 reference statements)
1
30
0
Order By: Relevance
“…Previous studies have reported that a wide range of blood sugar samples are needed to calculate GV, ranging from 1 to 5 times/day [6,7]. Moreover, a previous study using a continuous glucose monitoring system reported that a relatively small number of blood sugar samples in critically ill patients may underestimate GV [8]. When to determine GV in patients with sepsis is another important issue.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that a wide range of blood sugar samples are needed to calculate GV, ranging from 1 to 5 times/day [6,7]. Moreover, a previous study using a continuous glucose monitoring system reported that a relatively small number of blood sugar samples in critically ill patients may underestimate GV [8]. When to determine GV in patients with sepsis is another important issue.…”
Section: Introductionmentioning
confidence: 99%
“…We were not able to place CGM sensors or start enteral feeding until informed consent was given, and therefore we could have missed important data from the first hours after admission. Sensor and device problems occurred relatively frequently, and the use of a subcutaneous CGM is not standard of care in critically ill patients, although overall accuracy seems moderate to good . The enteral formulas used in this study differed in carbohydrate, protein, and fat content, as well as in qualitative terms (eg, more monounsaturated fatty acids in the LCF).…”
Section: Discussionmentioning
confidence: 94%
“…These limitations may prevent generalizability. 55 While the Sensors review focused on ICU CGM, we also highlighted the limited number of non-ICU CGM studies, a setting where there is less frequent patient monitoring. [43][44][45]56,57 Non-ICU patients, especially T1DM patients with a high likelihood of labile inpatient glycemic control 58 and hypoglycemic unawareness, may benefit most from CGM.…”
Section: Discussionmentioning
confidence: 99%